Lyme disease in Children: Diagnosis, Therapy and Prevention (III Part) - V.V. Mavrutenkov (Zaslavsky O.Yu., 2014)
The main indication for the initiation and evaluation of chemotherapy are clinical and epidemiological data, only the presence of serological markers of infection B.burgdorferi s.l. is not an absolute indication for the use of antibiotics. Rational antibiotic therapy allows for complete cure of the infection B.burgdorferi s.l. in most children and adults. Contact with ticks of the genus Ixodes is not mandatory indication for postexposure chemoprophylaxis for B.burgdorferi s.l. infection.